Pengaruh Model Pembelajaran Problem Based Learning (PBL) Dan Motivasi Belajar Terhadap Hasil Belajar IPA Siswa SD: indonesia - Zul Karnadi; Hartini Haritani; Muhammad Khaerul Wazni (Educatio, 2025)
The objective of this study is to examine the comparative effects of the Problem-Based Learning (PBL) model and the Conventional method on students' learning motivation. This research employs a quantitative approach with a Quasi-Experimental design. The study population consists of 30 sixth-grade students from SD Negeri 2 Denggen Timur, divided into two classes (VI.A and VI.B). Sampling was conducted based on learning motivation levels, resulting in 30 participants (15 with high motivation and 15 with low motivation). Hypothesis testing and data analysis revealed the following findings: A significant difference was found in learning outcomes between the PBL and Conventional groups. This was supported by an F(calculated) = 5.805, which exceeded the F(table) = 4.23 at a 0.05 significance level, leading to the acceptance of Ha and rejection of H0. An interaction effect was observed between instructional methods (PBL and Conventional) and learning motivation on academic performance. This was confirmed by an F(calculated) = 0.430 being greater than F(table) = 0.05, resulting in Ha being accepted and H0 rejected. High-motivation students taught using PBL achieved better results than those taught with the Conventional method. This was evidenced by t(calculated) = 1.892 > t(table) = 1.739 at a 0.05 significance level, thus supporting Ha and rejecting H0. Low-motivation students taught with PBL did not perform worse than those using the Conventional approach. The statistical result (t(calculated) = 1.833 > t(table) = 1.739) led to the rejection of Ha and acceptance of H0 In conclusion, PBL demonstrates varying impacts on learning outcomes, depending on students' motivation levels. Keywords: Problem-Based Learning Model, Conventional Learning, Learning Motivation, Learning Outcomes.